People who saw dark, fat devils with sharp teeth and bulging eyes – Charles Bonnet syndrome: a case series - A. ellepola (Sri Lanka Journal of Psychiatry, 2019)
Charles Bonnet syndrome (CBS) is characterised by visual hallucinations in people with visual impairment. There are different causes leading to CBS. This article describes 3 case reports of individuals who reported seeing ‘devils’ as visual hallucinations. The term ‘devil’ has a cultural significance in Sri Lanka. People still practice rituals related to ‘devils’, though this is now becoming less common. Psychopathology in psychiatric disorders can be influenced by cultural practices. This case series highlights the cultural influence on visual hallucinations and CBS.